Rare bird documentation form for Peregrine Falcon in Delaware County, 1984 - Bendorf, Carl J.et al (1984)
Rare bird documentation form for a Peregrine Falcon in east-central Delaware County, IA on April 6, 1984. Epson - sheet feed